2006
DOI: 10.1159/000097633
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators of Pre-Eclampsia in North Jordan: Is Dental Caries Involved?

Abstract: Background: Despite a huge body of published research, understanding the basic pathology that leads to pre-eclampsia is still incomplete. This study was conducted among women in north Jordan to determine factors associated with pre-eclampsia and to determine if dental caries was involved. Methods: A case-control study was carried out among women who delivered at Princess Badea Teaching Hospital, Irbid, North Jordan, between September 1, 2004 and January 1, 2005. 115 women with pre-eclampsia and 230 normotensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
4
1
Order By: Relevance
“…Thus, untreated dental caries may result in further inflammatory complications 33,34 , which could affect pregnancy outcomes 35 . Similarly, we hypothesized that dental caries may be associated with preterm birth and preeclampsia through an infectious process but found that there was no association among them, which is inconsistent with the results from other studies [13][14][15][16] . Furthermore, we did not find any significant difference according to the treatment for dental caries.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Thus, untreated dental caries may result in further inflammatory complications 33,34 , which could affect pregnancy outcomes 35 . Similarly, we hypothesized that dental caries may be associated with preterm birth and preeclampsia through an infectious process but found that there was no association among them, which is inconsistent with the results from other studies [13][14][15][16] . Furthermore, we did not find any significant difference according to the treatment for dental caries.…”
Section: Discussioncontrasting
confidence: 96%
“…It has been reported that pregnant women with periodontal diseases have an increased risk of preterm birth, preeclampsia, and delivering small-for-gestational-age (SGA) infants 11,12 . Similarly, several studies have reported a positive association between dental caries and adverse pregnancy outcomes, including preterm birth and preeclampsia [13][14][15][16] . However, these findings have been challenged by further studies 8,17 .…”
mentioning
confidence: 88%
“…The association between higher BMI and risk of preeclampsia reported in our study is consistent with that of previous studies based on both Western populations [ 17 21 , 23 , 26 , 28 30 , 32 36 , 38 ], and Asian populations [ 16 , 22 , 24 , 25 , 27 , 31 , 37 , 67 , 68 ]. Among the few previous studies that investigated the association between pre-pregnancy BMI and preeclampsia subtypes [ 14 , 19 , 30 , 38 ], their results suggested that overweight/obesity before pregnancy increased the risk of S-PE [ 14 , 19 ], M-PE [ 30 ], LOPE [ 30 , 38 ], but not EOPE [ 14 , 19 , 30 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Preeclampsia is also associated with other digestive systemrelated codes, such as dental caries (K029) and excessive attrition of the teeth (K30). Pregnant women with dental caries had a higher prevalence of preeclampsia compared to normotensive controls (adjusted odds ratio [aOR] 1.76, 95% CI 1.43À2.18) [66]. However, excessive attrition of the teeth might not be directly associated with preeclampsia, but with age, because attrition of the teeth was greater in the age group of 51À60 years compared to those in either the age group of 20À30 years or other younger age groups (p<0.003) [67].…”
Section: Discussionmentioning
confidence: 99%